Desain Sistem Penjernihan Air Berbasis Tenaga Surya untuk Pengolahan Air Bersih - Imaniah Sriwijayasih; Aang Wahidin; Priyambodo Nur Ardi Nugroho; Dika Rahayu Widiana; Sumardiono; Boedi Herijono; Rikky Leonard; Septaviola Dini Utami; Masaril Fatahilah; Cindy Putri Maharani (Jurnal Engine: Energi, Manufaktur, dan Material, 2025)
A slow sand filter is a natural water filtration system that uses fine quartz-rich sand as a filter medium. The filtration process runs by gravity at a slow and even speed over the entire surface of the sand, involving physical, biochemical and biological processes simultaneously. To achieve the desired water quality, the filtration system was designed using 8" PVC pipes. The main aim of this design is to mature the filter sand media and form an effective filter skin layer, so that biochemical and biological processes can take place optimally. In this design, silica sand and gravel media are used for physical and chemical processes, while ultraviolet lamps are used to eliminate E.Coli bacteria in biological processes. The design results show that the resulting product meets the standards of PERMENKES No. 16 of 2005. Irradiation using a UV lamp for one hour shows a reduction in E. Coli bacteria by 29/100 ml. This shows that the longer the exposure, the less bacteria contained in river water. This system can operate for 5 hours with the help of a 100 Wp solar panel, 12 volt 18 Ah battery, and 50 watt DC pump, even just with sunlight. The efficiency of solar panels is greatly influenced by the intensity of sunlight, so the higher the intensity of the sun, the higher the efficiency produced.